2011
DOI: 10.1177/0363546511413993
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative and Postoperative Sagittal Plane Hip Kinematics in Patients with Femoroacetabular Impingement during Level Walking

Abstract: The results supported the hypothesis that surgical intervention for FAI restores more normal patterns of gait and provides objective support that the surgical procedure is useful. The results help establish motion capture as a potential method for quantitatively assessing the outcome in FAI surgical interventions. The presence of abnormal reversals in hip flexion has been reported in end-stage hip osteoarthritis, and the presence of these reversals in FAI patients reinforces the idea of FAI being a precursor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
81
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 24 publications
9
81
2
1
Order By: Relevance
“…Neither of these studies demonstrated any impact of surgery on the kinetics of the hip. It is worth noting that Kennedy et [20,29] which may explain some of the differences in the results.…”
Section: Kinematics and Kinetics In Faimentioning
confidence: 88%
See 3 more Smart Citations
“…Neither of these studies demonstrated any impact of surgery on the kinetics of the hip. It is worth noting that Kennedy et [20,29] which may explain some of the differences in the results.…”
Section: Kinematics and Kinetics In Faimentioning
confidence: 88%
“…Surgical treatment resulted in an increased sagittal ROM and reduction in reverse hip flexion angle according to Rylander et al [20], but no improvement could be demonstrated by Brisson et al who looked at the effect of surgery on cam FAI [23]. Neither of these studies demonstrated any impact of surgery on the kinetics of the hip.…”
Section: Kinematics and Kinetics In Faimentioning
confidence: 96%
See 2 more Smart Citations
“…However, most movement studies examined sagittal plane imbalance [15][16][17] without examining interactions in the other planes of motion, which are used for functional activities of daily moving. Indeed, there is a lack of comprehensive understanding between shoulder and pelvic function based on the transverse plane.…”
Section: Introductionmentioning
confidence: 99%